Hepatocellular Carcinoma in Non-cirrhotic Liver Arises with a More Advanced Tumoral Appearance: A Single-Center Cohort Study - Demirtaş, Coşkun Özer; Tolu, Tuğba; Keklikkıran, Çaglayan; Özdoğan, Osman Cavit; Gündüz, Feyza (Turkish Journal of Gastroenterology, 2021)
Background: A small proportion of all hepatocellular carcinomas (HCCs) arise in a non-cirrhotic liver (NCL). However, our knowledge about the HCCs developing in a NCL is scarce. This study was undertaken to investigate the characteristics and survival course of this patient group. Methods: We retrospectively analyzed the database of patients with HCC at a tertiary center during a 10-year period (2009-2019). All demographic, clinical, laboratory, and tumoral features with survival outcomes were compared between the HCC-CL and HCC-NCL groups. Results: Out of 384 HCC cases, 11.2% (n = 43) had no cirrhosis. The dominant etiology in the HCC-NCL group was hepatitis B virus (n = 26, 60.5%), followed by non-alcoholic fatty liver disease (n = 10, 23.2%), and hepatitis C virus (n = 7, 16.3%). The maximum tumor diameter was approximately 2 times larger in the HCC-NCL group (HCC-NCL: 90 mm vs. HCC-CL: 46.5 mm, P < .001). The proportion of patients with vascular (HCC-NCL: 27.9% vs. HCC-CL: 8.6%, P < .001) and extrahepatic invasion (HCC-NCL: 14% vs. HCC-CL: 3%, P = .001) were prominently higher in the HCC-NCL group. Patients with HCC-NCL were less often detected in early-curable stages (BCLC 0-A) than those in the HCC-CL group (HCC-NCL: 16.3% vs. HCC-CL: 34.9%, P = .004). The overall survival was not different between the 2 groups (HCC-NCL: 19.4 ± 9.8 months vs. HCC-CL: 17.5 ± 2.3 months, P = .581). Conclusion: HCC in NCL is diagnosed at more advanced tumoral stages with larger tumor size and more often with vascular and extrahepatic spread. Despite the preserved liver functions, the overall survival is not prolonged in HCCs without cirrhosis, due to the late recognition.